2016
DOI: 10.1063/1.4939801
|View full text |Cite
|
Sign up to set email alerts
|

Self-deformation in a direct current driven helium jet micro discharge

Abstract: We report on the experimental observation of three dimensional self-deformation in an atmospheric micro discharge of the helium microjet through a tube into the ambient air upon a water electrode. The geometry of the discharge system is axial symmetric. While decreasing the discharge current, three dimensional collective motion of plasma filaments are directly observed. The three dimensional configuration of the discharge self changed from an axial symmetrical horn to a rectangular horn when the water acts as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…These SOPs can be described according to the parameters used in the studies reported in Table I, i.e., their size, their structural complexity (e.g., concentric rings, 19,34,36,37 strips, 34,37 spots, 19,34,37 or round area 19,34,35,37 ), and their dynamics, e.g., rotations. 19,34,36 In region I (I>26 mA), the bulk discharge appears diffusive in a pearshape 48,69 with an enlarged diameter close to the one of the SOPs formed on the liquid interface.…”
Section: Iiib2 Discussion On Sops Evolution With Discharge Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…These SOPs can be described according to the parameters used in the studies reported in Table I, i.e., their size, their structural complexity (e.g., concentric rings, 19,34,36,37 strips, 34,37 spots, 19,34,37 or round area 19,34,35,37 ), and their dynamics, e.g., rotations. 19,34,36 In region I (I>26 mA), the bulk discharge appears diffusive in a pearshape 48,69 with an enlarged diameter close to the one of the SOPs formed on the liquid interface.…”
Section: Iiib2 Discussion On Sops Evolution With Discharge Currentmentioning
confidence: 99%
“…• CBLD in noble gas on the cathode [20][21][22][23][24] • DBD with a semiconductor electrode 25 • Glow discharge at at 1 atm on the anode 26,27 and low pressure [28][29][30][31][32] • Pin liquid electrode discharge in the air with auxiliary gas [33][34][35] and without [36][37][38] .…”
Section: DCmentioning
confidence: 99%
“…To this end, different types of self-organization phenomena have been reported in a wide range of LTPs, such as dielectric barrier discharge [9], high frequency discharge [10], gas flow stabilized discharges [11,12] and resistively stabilized discharges [13]. It has been seen that a three-dimensional collective motion of plasma filaments can be observed [14]. The non-linear evolution of an argon discharge above the water electrode has been investigated [15].…”
Section: Introductionmentioning
confidence: 99%
“…Self-organized pattern transition on the liquid surface has attracted a tremendous amount of interests from the plasma community [17][18][19][20][21][22][23][24] because it encompasses a diversity of physical and chemical process at the plasma-liquid interface. Wilson et al observed [19] that a luminous spot formed on the gold or water anode produced circular patterns, while the spot rotation speed depended on the gas composition, discharge current, and discharge length.…”
Section: Introductionmentioning
confidence: 99%